Mobile device forensics: extracting and analysing data from an android-based smartphone - Abdul Aziz, Normaziah; Mokti, Fakhrulrazi; M. Nozri, Mohd Nadhar (Institute of Electrical and Electronics Engineers Inc., 2016)
The advancement of wireless technology and mobile devices have change our life tremendously. The number of smartphone users increases and majority people rely on it for communication and business related matters. While smartphones are used for positive aspects of our life, it is also used by criminals as medium for their modus operandi. Therefore, there are potential information stored in smartphones that can be used for digital evidence as part of an investigation. However, investigators may face challenges in extracting crucial information and the vital data stored in the smartphone. In this paper, we share on how we studied and experimented several methods on how data in smartphones can be extracted and analysed using the Sleuth Kit Autopsy. The aim of this work is to discover methods of extracting and analysing data from an Android based smartphone. We managed to obtain email, contact, messages, calendar, and images data that can be of used asdigital evidence in an investigation.